Entertainment journalism making it your career - Falk, Ben (Routledge, Taylor & Francis Group, 2018)
"Entertainment Journalism is a practical guide to one of the most highly visible areas of media practice. Drawing on 20 years' experience as an entertainment journalist, Ben Falk gives a comprehensive overview of journalistic reporting on the arts industries, with particular focus on film, music, reality TV and celebrity gossip. This is coupled with an extensive range of tips and tools to help students and young professionals hone the key skills required for a career in entertainment journalism. Interviews with industry professionals appear throughout, from current editors of the biggest entertainment brands, Hollywood bureau chiefs and critics to consumer publicists, multimedia content producers, live radio correspondents, video makers, TV presenters and social media specialists. Topics include: - breaking a story - interviewing techniques - working at press junkets and red carpet events - working with PRs - selling as a freelance - using social media for reporting and networking - breaking into the industry. With up-to-the-minute expert advice, accessibly written guidance on writing and reporting and invaluable perspectives from those within the entertainment world, this would be an instructive and insightful book for any aspiring showbiz journalist"--Provided by publisher.